THE APPLICATION OF TECHNOLOGY AND INFORMATION DEVELOPMENT IN ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) TO SHAPE PUBLIC AWARENESS - Valensia Utami, Putri (Edusight International Journal of Multidisciplinary Studies, 2024)
The legal system in Indonesia requires breakthroughs amidst the increasingly sophisticated technological developments today. Indonesia has Electronic Traffic Law Enforcement (ETLE) as one of the implemented technologies, which electronically records traffic violations. This is done due to limited human resources in traffic police and high legal needs. The use of electronic fines (E-Tilang) is also intended to address public complaints about the ineffectiveness of fines that enter the state treasury because the process of paying court tickets is often inefficient and time-consuming. The method used in this research applies a descriptive-qualitative method. The results of this study state that in practice, ETLE can only detect certain violations such as traffic sign violations. This shows how important it is to comply with traffic regulations and therefore, the ETLE system must be integrated with the national database, and to address these violations, a specific big data system must be created. Thus, it can be concluded that the enforcement of ETLE is still ineffective in addressing traffic violations on the roads in Indonesia.